Erosive Osteoarthritis: Presentation of a Treatment-Resistant Case - Hasan ULUSOY,; Gürkan AKGÖL,; Günseli KARACA ACET,; Arzu KAYA,; Ayhan KAMANLI, (Archives of Rheumatology, 2011)
Erosive osteoarthritis (EOA) is a progressive disease affecting the interphalangeal joints of the hand. It is also known as an inflammatory form of osteoarthritis. Pain, swelling, redness, warmth and limited function of the hand joints are commonly found in most patients with or without Heberden and Bouchard's nodes. Conventional radiographs of the hands show a combination of bony proliferation and erosions, which give characteristic patterns of the affected joints, known as “gull-wing” and “saw-tooth” deformities. Since there are no distinguishing laboratory findings between EOA and other common erosive interphalangeal arthropathies, radiographic features still have diagnostic value along with clinical presentation. Thus, recognition of the radiological manifestations may lessen the likelihood of misdiagnoses. A treatment-resistant case of EOA with marked and confusing inflammation is described in this report.